Single catalyst particle diagnostics in a microreactor for performing multiphase hydrogenation reactions. (5th March 2021) - Nieuwelink, Anne-Eva; Vollenbroek, Jeroen C.; Ferreira de Abreu, Andrea C.; Tiggelaar, Roald M.; van den Berg, Albert; Odijk, Mathieu; Weckhuysen, Bert M.
Abstract : The single particle hydrogenation of methylene blue over a Pd/SiO2 catalyst was monitored in a droplet-microreactor, using red/green/blue optical microscopy. Abstract : Since inter- and intra-particle heterogeneities in catalyst particles are more the rule than the exception, it is advantageous to perform high-throughput screening for the activity of single catalyst particles. A multiphase system (gas/liquid/solid) is developed, where droplet-based microfluidics and optical detection are combined for the analysis of single catalyst particles by safely performing a hydrogenation study on in-house synthesized hollow Pd/SiO2 catalyst microparticles, in a polydimethylsiloxane (PDMS) microreactor. A two-phase segmented flow system of particle-containing droplets is combined with a parallel gas-reactant channel separated from the flow channel by a 50 μm thick gas permeable PDMS wall. In this paper, the developed microreactor system is showcased by monitoring the Pd-catalyzed hydrogenation of methylene blue. A discoloration of blue to brown visualizes the hydrogenation activity happening in a high-throughput fashion on the single Pd/SiO2 spherical catalyst microparticles, which are encapsulated in 50 nL-sized droplets. By measuring the reagent concentration at various spots along the length of the channel the reaction time can be determined, which is proportional to the residence time in the channel. The developed experimental platform opens new possibilities for single catalyst particle diagnostics in a multiphase environment.